The Reconstruction of Religious Thought in Islam - Allama Muhammad Iqbal (Lahore Iqbal Academy Pakistan, 2018)
This major philosophic work by one of the most important Muslim and Western religious philosophers of the 20th century continues to exert an important literary, religious, and political influence today.
Keywords: Islam -- Philosophy and Religion -- Religious awakening--Islam -- Islam and philosophy